2007
DOI: 10.1017/s0950268806007758
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of cryptosporidiosis species in paediatric patients in Malawi

Abstract: We determined the incidence of cryptosporidiosis in children aged <5 years presenting with diarrhoea in an urban and rural hospital-based setting in Malawi. Stools were collected over a 22-month period during both rainy and dry seasons. A range of microscopic methods were used to determine the presence of Cryptosporidium spp. oocysts. Species determination was by polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) of oocyst-extracted DNA using 18S rRNA and COWP gene loci. Cryptosporid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
69
2
4

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(80 citation statements)
references
References 36 publications
5
69
2
4
Order By: Relevance
“…oocysts in their stools was found to be 11.0 %, a surprisingly high rate given the lack of symptoms in these individuals. This rate is comparable to the prevalence observed in diarrheic individuals which vary from 3 to 10 % according to HIV prevalence (Wumba et al 2012;Gatei et al 2006;Morse et al 2007). The existence of this reservoir therefore constitutes a potential risk for the infection of malnourished and immunocompromised individuals.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…oocysts in their stools was found to be 11.0 %, a surprisingly high rate given the lack of symptoms in these individuals. This rate is comparable to the prevalence observed in diarrheic individuals which vary from 3 to 10 % according to HIV prevalence (Wumba et al 2012;Gatei et al 2006;Morse et al 2007). The existence of this reservoir therefore constitutes a potential risk for the infection of malnourished and immunocompromised individuals.…”
Section: Discussionsupporting
confidence: 80%
“…This species is a strictly human parasite and PlaineOrety is a district of Libreville in which the human population rarely comes into contact with the C. parvum parasite non human reservoir. Moreover, in tropical areas, most surveys on the general population, and even on patients with diarrhea, have shown that C. hominis predominates (Wumba et al 2012;Gatei et al 2006;Morse et al 2007;Walker al. 2010).…”
Section: Discussionmentioning
confidence: 99%
“…C. andersoni is a gastric parasite which has been associated with reduced milk yield in dairy cattle and decreased weight gain in post weaned calves (Olson et al 2004) and is occasionally detected in humans (Leoni et al, 2006;Morse et al, 2007;Waldron et al, 2011;Agholi et al, 2013;Jiang et al, 2014;Liu et al, 2014). Two studies in China by the same research group have reported that C. andersoni was the most prevalent Cryptosporidium species detected in humans Liu et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Malawian child was also largely based on RFLP analysis, 29 which needs to be confirmed by DNA sequencing because DraI and AseI RFLP is mainly used in species differentiation and C. muris may also share the same pattern. Although the microscopic examination of feces still remains the mainstay of laboratory diagnosis of cryptosporidiosis, the results indicate that PCR is more effective than microscopic examination for the detection of coccidiosis.…”
Section: Agholi Hatam and Motazedianmentioning
confidence: 99%